Towards Comprehensive Women's Healthcare in Sub-Saharan Africa: Addressing Intersections Between HIV, Reproductive and Maternal Health - Kendall, Tamil (J Acquir Immune Defic Syndr, 2014)
This themed supplement to JAIDS: Journal of Acquired Immune Deficiency Syndromes focuses on the critical intersections between HIV, reproductive, and maternal health services in the health systems of sub-Saharan Africa. The epidemiology of HIV among women of reproductive age on the sub-continent demands a holistic conceptualization and comprehensive approaches to ensure that HIV, reproductive, and maternal health are optimally addressed. Yet, in many instances, the national and global responses to these health issues remain siloed. Women's health needs and new global and national guidelines for HIV treatment raise important policy, programmatic, and operational questions regarding service integration, scale-up, and health systems functioning. In June 2013, the Maternal Health Task Force at the Harvard School of Public Health, the United States Agency for International Development, and the United States Centers for Disease Control and Prevention convened an international technical meeting of researchers, policymakers, and practitioners to discuss the existing evidence base about the interconnections between HIV, reproductive, and maternal health and identify the most important knowledge gaps and research priorities. The articles in this special issue deepen and expand on those discussions by (1) providing empirical evidence about challenges, (2) identifying how improving clinical care and models of service delivery, strengthening health systems, and addressing social dynamics can contribute to better outcomes, and (3) mapping future research directions. Together, these articles underscore that new policy frameworks and integrated approaches are necessary but not sufficient to address health system challenges. Addressing the multiple needs of women of reproductive age who are living with HIV or are at risk of acquiring HIV is a complex undertaking that requires improved access to, utilization and quality of comprehensive women's healthcare. Continued evaluation and knowledge generation are needed to ensure that potential health gains are actualized.